Dietary Intake of Total Carbohydrates, Sugar and Sugar-Sweetened Beverages, and Risk of Inflammatory Bowel Disease: A Systematic Review and Meta-Analysis of Prospective Cohort Studies - Khademi, Zeinab; Milajerdi, Alireza; Larijani, Bagher; Esmaillzadeh, Ahmad (Frontiers in Nutrition, 2021)
Objectives: No earlier study has summarized findings from prospective cohort studies on the association of dietary carbohydrates, sugar, and sugar-sweetened beverages (SSBs) consumption and risk of inflammatory bowel disease (IBD). The current study was done to quantitatively summarize earlier information from prospective cohort studies on the link between dietary carbohydrates, sugar, and SSBs intake with risk of IBD. Methods: Relevant studies published up to June 2021 were searched through PubMed, Medline, SCOPUS, EMBASE, and Google Scholar with the use of relevant keywords. All prospective cohort studies investigating the association of dietary carbohydrates, sugar, and SSBs consumption with risk of IBD were included. Results: Combining 5 effect sizes from 4 cohort studies, no significant association was found between dietary intake of carbohydrates and risk of ulcerative colitis (UC) (RR: 1.22; 95% CI: 0.70–2.14). The same findings were obtained for risk of Crohn's disease (CD) (RR: 1.06; 95% CI: 0.64–1.75) based on 4 studies with 5 effect sizes. A significant positive association was observed between sugar intake and risk of UC (RR: 1.59; 95% CI: 1.15–2.20), as well as CD (RR: 1.90; 95% CI: 1.06–3.41) when 5 effect sizes from 4 cohort studies were combined. The overall effect size, based on 4 estimates, revealed no significant association between SSBs consumption and risk of UC (RR: 1.02; 95% CI: 0.92–1.12) and CD (RR: 1.22; 95% CI: 0.91–1.64). Conclusions: Summarizing earlier studies, sugar intake was found to be associated with increased risk of IBD and its subtypes. Any significant association between dietary intake of carbohydrates and SSBs and risk of IBD and its subtypes was not found.